Dickkopf 3 attenuates xanthine dehydrogenase expression to prevent oxidative stress‐induced apoptosis. (15th March 2017) - Qui, Shuang; Kano, Junko; Noguchi, Masayuki
Abstract : Dickkopf (DKK) 3 is a DKK glycoprotein family member that controls cell fate during embryogenesis and exerts opposing effects on survival in a cell type‐dependent manner; however, the mechanisms governing its pro‐apoptosis versus pro‐survival functions remain unclear. Here, we investigated DKK3 function in Li21 hepatoma cells and tPH5CH immortalized hepatocytes. DKK3 knockdown by siRNA resulted in reactive oxygen species accumulation and subsequent apoptosis, which were abrogated by administration of the antioxidant N‐acetyl‐cysteine. Moreover, forced DKK3 over‐expression induced resistance to hydrogen peroxide (H2 O2 )‐induced apoptosis. Expression analysis by cDNA microarray showed that xanthine dehydrogenase ( XDH ) expression was significantly lower in Li21 and tPH5CH DKK3 ‐over‐expressing cells in response to H2 O2 treatment when compared to that in their respective mock‐transfected controls, whereas a marked increase was observed in H2 O2 ‐treated DKK3 knockdown cells. Thus, these data suggest that DKK3 promotes cell survival during oxidative stress by suppressing the expression of the superoxide‐producing enzyme XDH. Abstract : DKK3 promotes cell survival during oxidative stress by suppressing the expression of the superoxide‐producing enzyme XDH.